Minimally invasive transcrestal sinus floor elevation with deproteinized bovine bone or β‐tricalcium phosphate: a multicenter, double‐blind, randomized, controlled clinical trial. (2nd January 2014) - Trombelli, Leonardo; Franceschetti, Giovanni; Stacchi, Claudio; Minenna, Luigi; Riccardi, Orio; Di Raimondo, Rosario; Rizzi, Alessandro; Farina, Roberto
Abstract Aims To evaluate the outcomes of transcrestal sinus floor elevation (tSFE) performed with a minimally invasive procedure (Smart Lift technique) combined with the additional use of deproteinized bovine bone mineral (DBBM) or β‐tricalcium phosphate (β‐TCP). Methods In a multicenter randomized controlled trial, 38 sites in 38 patients were treated with the Smart Lift technique in association with DBBM (n = 19) or β‐TCP (n = 19). The extent of the sinus lift (SL) and the height of the graft apical to the implant apex (aGH) were assessed on periapical radiographs taken immediately after surgery and at 6 months following surgery. Results (i) Substantial aGH and SL were observed immediately after surgery and at 6 months, with no significant differences between DBBM and β‐TCP groups; (ii) a significant graft remodelling was observed from post‐surgery to 6‐months in the β‐TCP group and (iii) limited incidence of complications as well as limited post‐operative pain and discomfort were associated with the use of both graft materials. Conclusions The Smart Lift technique in conjunction with the additional use of either DBBM or β‐TCP may provide a substantial elevation of the maxillary sinus floor along with limited post‐surgical complications and post‐operative pain/discomfort.